2021
DOI: 10.3390/ijerph18052766
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics and Burden of Stroke and Epilepsy in Sub-Saharan Africa: Experience from a Longstanding Health Programme

Abstract: Eighty percent of people with stroke live in low- to middle-income nations, particularly in sub-Saharan Africa (SSA) where stroke has increased by more than 100% in the last decades. More than one-third of all epilepsy−related deaths occur in SSA. HIV infection is a risk factor for neurological disorders, including stroke and epilepsy. The vast majority of the 38 million people living with HIV/AIDS are in SSA, and the burden of neurological disorders in SSA parallels that of HIV/AIDS. Local healthcare systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In response, health service provision underwent a significant reorganization to address COVID-19 pressures. The impact on services for people with non-communicable diseases, especially those with associated risk, has been considerable [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…In response, health service provision underwent a significant reorganization to address COVID-19 pressures. The impact on services for people with non-communicable diseases, especially those with associated risk, has been considerable [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…There is a pressing need to invest in relevant training to improve health, social, quality of life and economic outcomes in sub-Saharan Africa [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in SSA, about 22.9 million people are living with HIV (57/100 million); a study has shown that 4%‐17% of people living with HIV develop new seizures. 88 …”
Section: About Tropical Epilepsymentioning
confidence: 99%